The Correlation Between Students’ Personality (Extrovert and Introvert) and Their Reading Comprehension Achievement - Satria Adi Pradana; Al Hakim Bani Ismail (UNIB Press, 2022)
The students struggled with reading due to a lack of vocabulary and boredom when attempting to comprehend a reading text. Besides, the Teacher's technique did not match the student's personalities, so they did not follow the instructions given by the Teacher in the reading learning process. As a result, many students at MAN 1 Pesisir Barat Lampung got underscore in reading. This study aimed to determine whether there was a relationship between the personality traits of students (extrovert and introvert) and their reading comprehension success in the tenth grade of MAN 1 Pesisir Barat Lampung in the academic year 2020/21. This research used a correlation research design. The population of this research was the tenth grade of MAN 1 Pesisir Barat Lampung. The sample of this research was two classes, X Science 1 and 2, consisting of 77 students from those two classes. The data is collected by using personality questionnaires and reading comprehension tests. There were 20 questions for the personality questionnaires exam and 40 questions for the reading comprehension test, which had been verified. After collecting data for both variables, SPSS version 21 with the Pearson Correlation Formula was used to analyze the data. After doing the hypothetical test, the result showed that the value of significant generated Sig (P-value) = 0.006 < ɑ = 0.05. As a result, H0 was rejected, and H1 was accepted. Thus, it can be concluded that there was a correlation between students' personalities (extrovert and introvert) and their reading comprehension achievement in the tenth grade of MAN 1 Pesisir Barat Lampung in the academic year 2020/2021. Then, the coefficient correlation between students' personality and their reading comprehension achievement was 0.749, which means that the correlation of both variables was high and positive. Keywords: Correlation Research Design; Personality; Reading Comprehension Achievement.